2019
DOI: 10.3389/fgene.2019.00529
|View full text |Cite
|
Sign up to set email alerts
|

Genome and Phylogenetic Analysis of Genes Involved in the Immune System of Solea senegalensis – Potential Applications in Aquaculture

Abstract: Global aquaculture production continues to increase rapidly. One of the most important species of marine fish currently cultivated in Southern Europe is Solea senegalensis , reaching more than 300 Tn in 2017. In the present work, 14 Bacterial Artificial Chromosome (BAC) clones containing candidate genes involved in the immune system ( b2m , il10 , tlr3 , tap1 , tnf α, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 89 publications
1
8
0
Order By: Relevance
“…Flatfish genome comparisons have demonstrated a high degree of conservation at macrosynteny level 5 , 57 , 58 . Our data confirmed that most of chromosomes matched one-by-one with different chromosomes of C. semilaevis supporting this high conservation observed in other flatfish.…”
Section: Discussionmentioning
confidence: 99%
“…Flatfish genome comparisons have demonstrated a high degree of conservation at macrosynteny level 5 , 57 , 58 . Our data confirmed that most of chromosomes matched one-by-one with different chromosomes of C. semilaevis supporting this high conservation observed in other flatfish.…”
Section: Discussionmentioning
confidence: 99%
“…The largest metacentric pair has been proposed as a sex proto-chromosome pair, due to different lines of evidence, such as the accumulation of genes related to sex [ 35 , 37 ], existence of Robertsonian fusion [ 33 , 36 ], evidence of recurrent chromosomal inversions [ 36 , 37 ] and accumulation of repetitive sequences [ 28 , 36 ]. Recently, an analysis of the 24 genes related to the immune system in Senegalese sole showed some tendency to group in a few chromosomes, which could provide an evolutionary advantage [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through the FISH-BAC technique, the acquisition of the cytogenetic map of the species has been deepened and integrated with physical maps, by using different genes of interest for the cultivation of the species. Similarly, it has been possible to characterize and locate the BAC clones with other types of sequences of interest, such as miRNAs or transposons [ 6 , 28 , 33 , 34 ]. As a result of these studies, evidence has accumulated that the pair of major metacentric chromosomes of S. senegalensis could be a pair of sex proto-chromosomes, which have followed a specific evolutionary pattern involving, among other events, Robertsonian fusion [ 33 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative genomics of orthologous sequences located in the karyotype has opened new ways to detect karyotype differences because it allows comparisons to be made between species, genera, and even families, providing a more detailed overview of the evolutionary changes in the karyotype. It also allows us to overcome serious limitations of cytological studies such as genetic disruption of meiotic pairing and indistinguishable chromosomes [3,4].…”
Section: Introductionmentioning
confidence: 99%